The Influence of Company Size, Managerial Ownership, and Institutional Ownership on Company Value: An Empirical Study on Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange for the 2021–2024 Period - Wahyuni Seri; Endarwati Endarwati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to evaluate the influence of company size, managerial ownership, and institutional ownership on company value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. In this study, the value of the company is expressed in the form of a Price to Book Value (PBV) ratio. The approach used is quantitative with the type of associative research. The selection of samples was carried out purposively and resulted in 80 companies as research objects. The test results showed that the three independent variables, either individually or together, did not have a significant influence on the company's value. This is evidenced by the significance value of the F test of 0.418 and the coefficient of determination (R²) of 0.036, which indicates that the model is only able to explain 3.6% of the total variation in the company's value. These findings indicate that the internal factors studied have not been able to explain the change in company values substantially, so exploration of other variables in follow-up studies is needed to gain a more comprehensive understanding.